Decoupling Responses of Phyllosphere and Rhizosphere Bacterial Communities to Spatiotemporal Environmental Changes - Chen, Wei; Zhu, Biao; Yang, Caiqin; Wei, Chunqiang; He, Yifan; Zheng, Long; Liu, Xiaoyan; Yang, Jingyuan; Tedersoo, Leho; Lu, Xinmin; Wilschut, Rutger A. (Global change biology, 2025)
ABSTRACT Understanding and predicting how plant‐associated microbes respond to environmental changes is of key importance to understanding future plant performance. Yet, how aboveground and belowground plant‐associated microbial communities, which may interactively affect plant performance, simultaneously respond to environmental changes, remains unknown. To fill this gap, we monitored temporal changes of phyllosphere and rhizosphere bacterial communities of three perennial species at 18 sites spanning a 1500 m elevational gradient. We showed distinct temporal trajectories of these community types, likely reflecting their differential responses to abiotic (e.g., air moisture) and biotic (e.g., plant specific leaf area) environmental factors. Further, using a transplantation experiment with the same plant species and their rhizosphere soils, we show that a portion of bacterial taxa from transplanted communities persisted in plants' rhizosphere 2 months after being transplanted to warmer sites. In contrast, phyllosphere communities were primarily harbored by taxa colonizing from local communities. Notably, the relative growth rate of transplanted plants at new versus original sites was positively correlated with the compositional dissimilarity between their phyllosphere and rhizosphere bacterial communities. Together, our results highlight the role of compartment‐by‐environment interactions in shaping the plant holobiome communities and emphasize the need to understand the impacts of such interactions on plant performance under global change. By integrating a comprehensive field survey with a transplantation experiment across elevations, we showed decoupling responses of rhizosphere and phyllosphere bacterial communities in three plant species to both temporal and spatial variations in enviroments. The decoupling responses of these communities profoundly affected the performance of transplanted plants. Our findings highlighted the importance of compartment‐by‐environment interactions in shaping plant‐microbial interactions.